Analyzing Factors Affecting the Purchase Decision of Shopee Users in Bekasi - Syahtidar, Nanda; Suherman, Suherman; Siregar, M. Edo S. (Interdisciplinary Social Studies, 2022)
Background: The emergence of information and communication technologies such as the internet has opened up new opportunities for the spread and development of the use of online transactions. Aim: This study aims to determine the influence of brand image, price, word of mouth, and advertisement to purchase decisions of Shopee users. Method: The method of data collection is using the survey method with Likert-type purposive sampling. The object of this research is 200 respondents who are Shopee users in Bekasi. This research used SPSS software version 24 and SEM (Structural Equation Modelling) AMOS version 24 for data analysis. The fit value of the model with a probability level of 0.525, CMIN/DF value of 0.988, GFI value of 0.928, AGFI value of 0.907, RMSEA value of 0.000, TLI value of 1.001, and CFI value of 1.000. Findings: The result of the hypothesis show: (1) brand image has a positive and significant effect on purchase decision, (2) price has a positive and significant effect on purchase decision, (3) word of mouth has a positive and significant effect on purchase decision, (4) advertisement has a positive and significant effect on the purchase decision.